Islamic groups in Pakistan, A study of the origin and political role 1941-1958. (Journal of Misan Researches, 2024)
Jama’at-i-Islami is an Islamic political group founded in Lahore in 1941 by Abul A'la Maududi, an Islamic thinker who saw Islam as providing a political ideology that transcended strict religious discipline. Initially, Jamaat-e-Islami opposed the partition of the Indian subcontinent and wich lwads to establishment of an Islamic state throughout India. The independence of Pakistan in 1947 prompted Jamaat-e-Islami to campaign peacefully for the transformation of Pakistan into an Islamic system of government. The Jamaat-e-Islami campaigned primarily for an Islamic constitution and evolved into an Islamic lobby for the establishment of an Islamic state. It is credited with introducing the Islamic element into the political and constitutional structure of Pakistan and keeping the cause of Islam alive in Pakistani political life. The Jamaat's style, ideas and policies regarding the Islamic constitution of Pakistan emerged from 1947 to 1956.